A review on the behavior of FRP-reinforced ultra-high-performance concrete tubes - Al-Tayeb, Mustafa Maher; Hamad, Rami J. A.; Tayeh, Bassam A.; Aldahdooh, Majed A. A.; Altwair, Nurdeen M.; Zeyad, Abdullah M. (John Wiley and Sons Inc, 2025)
This paper reviews previous research on ultra-high-performance concrete (UHPC) tubes confined with fiber-reinforced polymer (FRP). It summarizes current studies and provides insights for future research. UHPC-filled FRP tubes with different fiber types and tube thicknesses were tested to investigate their mechanical properties. It focuses on how different FRP types and numbers of FRP layers affect failure modes, mechanical properties, energy absorption, and ductility. Generally, the specimens failed by rupture of the tube at or near the midheight. Similar to conventional concrete, test results showed significant enhancements in the ultimate strength and strain of UHPC compared with its unconfined counterpart. For the same level of FRP confinement, the highest increase in ultimate strength is observed in CFRP-confined UHPC columns, as CFRP has higher stiffness compared to other FRP types such as AFRP and GFRP. The paper also examines models used to simulate experimental results, helping to understand UHPC behavior under FRP confinement better.
Keywords: confined tubes; fiber-reinforced polymer; ultra-high-performance concrete